Determinar la estructura horizontal del bosque de terraza baja de la Comunidad Nativa Nuevo Trujillo. Distrito del Maquía, Rio Ucayali. Loreto – Perú. 2022 - Vela Pacaya, Carlos Augusto (2024)
In the study carried out in PC1, the low terrace forest of the Nuevo Trujillo native community. Maquía District, Ucayali River. Loreto – Peru. A total of 292 trees were recorded, grouped into 06 commercial forest species and 05 botanical families, where the Malvaceae families contain the largest number of species (two species), followed by the “Moraceae”, “Vochysiaceae”, “Rubiaceae”, “Sapotaceae” families (one species each). Volume by diameter class, showing the calculation of 7,855 m3/h in the of a total of 221,813 h. The “Capinurí” species (6,903 m3/h), reports the highest volume; On the contrary, “Quillosisa” (0,301 m3/h), “Lupuna” (0,212 m3/h), “Capirona” (0,212 m3/h), “Huimba” (0,207 m3/h) and “Quinilla” (0,020 m3/h) show lower volume. Also, it is necessary to indicate that the diameter class of 100 cm or more (2,569 m3/Ha) contains the highest volume/Ha, followed by 80 cm to 89 cm); while the diameter classes from 50 cm to 59 cm (0,080 m3/h) have a lower volume. The results indicate that this forest contains a total volume of 1742,400 m3 for the entire area (221,813 Ha). “Capinurí” (1531,180 m3), contains the highest volume value; On the contrary, “Huimba” (45,930 m3) and “Quinilla” (4.51 m3) have a lower volume. IV. The Capinurí species (196.51%) is the most ecologically important in the forest, which make up a total of 196.51% of participation in the structure of this forest. Furthermore, it can be stated that two species report little participation with less than 21% of IVI, which are represented by “Lupuna” (15.81%), and “Quinilla” (4.72%).